Benefits and drawbacks of food and dairy waste co-digestion at a high organic loading rate: A Moosburg WWTP case study. (15th July 2019) - Sembera, Claire; Macintosh, Catherine; Astals, Sergi; Koch, Konrad
Graphical abstract: Highlights: The Moosburg WWTP incorporates 65% by VS of co-substrates. 186% OLR increase from co-substrates resulted in 300% increase in CH4 production. Solids accumulation of 5 m 3 /month from high ratio of food waste. 65% increase in nitrogen backload from co-substrate addition. Alternative method for determining gate-fees proposed. Abstract: Anaerobic co-digestion (AcoD) is a key technology in reframing organic waste as a viable energy source. A lack of documented experience on full-scale AcoD at wastewater treatment plants (WWTPs) has created a bottleneck in AcoD implementation, which is further tightened by the focus of existing AcoD studies being on low co-substrate loading (<50%) and the obtainable benefits. This study aims to fill this gap by investigating the drawbacks and benefits of high-ratio co-substrate dosing of food and dairy wastes at the Moosburg WWTP (Germany) from 2014 to 2017. The Moosburg WWTP co-digests sewage sludge, food waste, and dairy wastes at a 35:47:18 ratio by volatile solids (organic loading rate (OLR) of 3.0 kgVS /(m 3 ·day)). During the study period, this high co-substrate dosing increased the methane potential by 300 ± 50%. The corresponding high methane yield significantly increased the on-site electricity production, resulting in energy neutrality in 2014–2015. The corresponding economic gain from gate fees was 48, 000 ± 5, 000 € per year. The observed drawbacks included solids accumulation inside the digester (5 m 3 /month), high nitrogen backload (65% increase from co-substrate addition), reduced retention time (loss of 1.18 days/year from solids accumulation), and reduced dewaterability. The high nitrogen content in the centrate is treated by sequential batch reactors (SBRs), using lactose as the carbon source for denitrification. This study presents an alternative approach for determining gate fees based on the economic gains from inherent methane content, which identified waste milk, lactose and grease trap sludge as the most profitable co-substrates.